Inside Cover: 5′‐(E)‐Vinylphosphonate: A Stable Phosphate Mimic Can Improve the RNAi Activity of siRNA–GalNAc Conjugates (ChemBioChem 11/2016). (3rd June 2016) - Parmar, Rubina; Willoughby, Jennifer L. S.; Liu, Jingxuan; Foster, Donald J.; Brigham, Benjamin; Theile, Christopher S.; Charisse, Klaus; Akinc, Akin; Guidry, Erin; Pei, Yi; Strapps, Walter; Cancilla, Mark; et al.
Abstract : The inside cover picture shows the benefit of 5'‐(E)‐vinylphosphonate (VP), a stable phosphate mimic over 5′‐phosphate (5′‐P) in improving the siRNA‐GalNAc conjugate loading into the RNA‐induced silencing complex (RISC). The siRNA conjugated to trivalent N ‐acetylgalactosamine (GalNAc) is recognized by the asialoglycoprotein receptor (ASGPR) expressed on the surface of a hepatocyte for cellular uptake via endocytosis. Unlike natural phosphate, the 5′‐VP on siRNA‐GalNAc is not removed in endosome/lysosomes. The presence of 5′‐VP on siRNA promotes RISC loading thereby improving the in vivo activity. On the other hand, the loss of 5′‐P from siRNA‐GalNAc hampers RISC loading. More information can be found in the communication by V. Jadhav et al. onpage 985 in Issue 11, 2016 (DOI:10.1002/cbic.201600130 ).